Antipredator phenotype in crucian carp altered by a psychoactive drug. Issue 14 (14th June 2021) - Vinterstare, Jerker; Brönmark, Christer; Nilsson, P. Anders; Langerhans, R. Brian; Berglund, Olof; Örjes, Jennie; Brodin, Tomas; Fick, Jerker; Hulthén, Kaj
Abstract: Predator‐inducible defenses constitute a widespread form of adaptive phenotypic plasticity, and such defenses have recently been suggested linked with the neuroendocrine system. The neuroendocrine system is a target of endocrine disruptors, such as psychoactive pharmaceuticals, which are common aquatic contaminants. We hypothesized that exposure to an antidepressant pollutant, fluoxetine, influences the physiological stress response in our model species, crucian carp, affecting its behavioral and morphological responses to predation threat. We examined short‐ and long‐term effects of fluoxetine and predator exposure on behavior and morphology in crucian carp. Seventeen days of exposure to a high dose of fluoxetine (100 µg/L) resulted in a shyer phenotype, regardless of the presence/absence of a pike predator, but this effect disappeared after long‐term exposure. Fluoxetine effects on morphological plasticity were context‐dependent as a low dose (1 µg/L) only influenced crucian carp body shape in pike presence. A high dose of fluoxetine strongly influenced body shape regardless of predator treatment. Our results highlight that environmental pollution by pharmaceuticals could disrupt physiological regulation of ecologically important inducible defenses. Abstract : We examined short‐ and long‐term effects of fluoxetine on the anti‐predator phenotype in crucian carp. We found effects of fluoxetine on both behaviour and body shape, highlighting both proximate mechanism behind external defence regulation but also that environmental pollution by pharmaceuticals could disrupt physiological regulation of ecologically important inducible defences.